1998
DOI: 10.1046/j.1469-7580.1998.19240507.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and ultrastructural observations on the rat liver after two‐thirds partial hepatectomy*

Abstract: Rat liver ultrastructure was investigated after partial hepatectomy (PH), by scanning and transmission electron microscopy. Portal pressure was monitored before and after PH and, after killing performed at 6, 12, 24, 48 h and 10 d, regenerating livers were fixed by portal vein perfusion under haemodynamic conditions identical to those existing in vivo. An early and persistent increase in portal pressure after PH was found (P 0.01 for normal vs sham-operated controls). Ultrastructural study showed sinus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
32
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 34 publications
6
32
0
2
Order By: Relevance
“…10,[33][34][35] At this time, we observed that fenestration diameter and porosity increases significantly in zone 1. Fenestration diameter does not increase as markedly in zone 3, and this could be a result of the pressure differences reported between the 2 zones.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…10,[33][34][35] At this time, we observed that fenestration diameter and porosity increases significantly in zone 1. Fenestration diameter does not increase as markedly in zone 3, and this could be a result of the pressure differences reported between the 2 zones.…”
Section: Discussionmentioning
confidence: 71%
“…36 Increased portal pressure resulting from 70% PHx has been shown to persist at least until 72 hr after resection. 10,34,35,37 Our results indicate that increased portal pressure is probably not the only effector of porosity, because increased porosity was not maintained throughout the reported period of elevated pressure (Figs. 1-3).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations